Development of Social Arithmetic Problem Solving Ability Assessment Tool for Junior High School Students - Baso Intang Sappaile; Abdul Rahman; Fakhiratunnisa Fakhiratunnisa; Tajuddin Tajuddin (PT ARRUS Intelektual Indonesia, 2023)
This study aims to produce an assessment tool that is able to measure social arithmetic problem solving skills in junior high school students. This type of research is a type of development research. The subjects in this study were 81 students of SMPN 25 Barru. The results showed that the assessment tool for social arithmetic problem solving ability consisted of grids, test instruments, and scoring guidelines. In the test grid there are eight indicators of questions that cover all social arithmetic material in the 2013 curriculum for junior high school students. The instrument consists of ten items developed from the eight indicators in the test grid. The scoring guide, on the other hand, contains standards for scoring students based on the types of problems they solve. The research tool has been declared valid and reliable with a reliability coefficient of 0.9. In terms of difficulty level, there are 7 questions in the medium category, 1 question in the difficult category, and 2 questions in the easy category. From the aspect of discriminating power, there are 5 questions in the sufficient category, 3 questions in the good category and 2 questions in the very good category.